Influence of intercropping on growth and yield of cassava (Manihot esculenta Crantz) - Esiape, Collins (2016)
A thesis submitted to the Department of Crop and Soil Sciences, Faculty of Agriculture, College of Agriculture and Renewable Natural Resources, Kwame Nkrumah University of Science and Technology, Kumasi, Ghana in partial fulfillment of the requirement for the award of Master of Philosophy Degree in Agronomy, (Crop Physiology), 2015